A case report on mad (wild) honey intoxication - Shrestha, B; Paudel, P (Journal of Chitwan Medical College, 2015)
Mad honey disease is one of the rarest disease caused by consumption of leaves, flowers or its products such as honey. The toxicity is secondary to consumption of honey produced by pollen and nectars found in rhodenderon species. Mad honey is mostly found in Black Sea and south east region of Turkey. However 3 cases has been reported in the few hospitals in Kathmandu, Nepal. However until now there is not such case reports reported in Chitwan, mid central region of Nepal. Here, we report a case of 40 years old man who reported to our emergency department with complaint of dizziness, vomiting and blackout with first examination of bradycardia and hypotension in consequences of mad honey consumption.